"Infrastructure to 2030 : mapping policy for electricity, water and transport" - Organisation for economic co-operation and development (Paris, 2007)
Infrastructure systems play a vital role in economic and social development. Increasingly interdependent, they are a means towards ensuring the delivery of goods and services that promote economic prosperity and growth and contribute to quality of life. Demand for infrastructure is set to continue to expand significantly in the decades ahead, driven by major factors of change such as global economic growth, technological progress, climate change, urbanisation and growing congestion. However, challenges abound: many parts of infrastructure systems in OECD countries are ageing rapidly, public finances are becoming increasingly tight and infrastructure financing is becoming more complex. The looming "infrastructure gap" needs to be closed. Where will new sources of finance come from and what role will the private sector play? How can infrastructure systems be managed more effectively and efficiently? Will the financial, organisational, institutional and regulatory arrangements (the "business models") currently in place be able to respond adequately to the complex challenges they face, and are they sustainable over the longer term? This book assesses the future viability of current "business models" in five infrastructure sectors: electricity, water, rail freight, urban mass transit and road transport. It proposes policy recommendations that aim to enhance capacity to meet future infrastructure needs, including measures that could be taken by governments both collectively and individually to create more favourable institutional, policy and regulatory frameworks. This book is the second of two publications on the future of infrastructure development. It follows Infrastructure 2030: Telecom, Land Transport, Water and Electricity published in 2006.